2019
DOI: 10.1093/mmy/myz056
|View full text |Cite
|
Sign up to set email alerts
|

Viability of pathogenic dermatophytes during a 4-week treatment with 1% topical luliconazole for tinea pedis

Abstract: The viability of pathogenic fungi in the scale was investigated during topical administration of 1% luliconazole (LLCZ). Thirteen tinea pedis patients found to be positive on KOH examination were assessed by mycological examinations and quantitative real-time polymerase chain reaction (PCR) targeted internal transcribed spacer (ITS) in ribosomal RNA gene at the initial visit and after 2 and 4 weeks of treatment. Assays showed that the average copy number of ITS DNA had significantly decreased to 22.9% at 2 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 19 publications
1
22
1
Order By: Relevance
“…According to the recent increase in dermatophytosis and emergence of antifungal drug resistance, performing reliable AFST is essential, particularly for chronic and recurrent dermatophytosis 38 . In the current study, LUL (GM MIC 0.03‐0.05 μg mL ‐1 ) was the most effective agent against all tested isolates, the result which is in agreement with that of previous studies conducted in Iran, Japan and India 15,24,34,39 . Koga et al 38 showed that the MIC 90 values of LUL for T rubrum and T mentagrophytes were lower than those for other isolates; however, in the present study, it was the most effective drug against all dermatophyte isolates 40 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to the recent increase in dermatophytosis and emergence of antifungal drug resistance, performing reliable AFST is essential, particularly for chronic and recurrent dermatophytosis 38 . In the current study, LUL (GM MIC 0.03‐0.05 μg mL ‐1 ) was the most effective agent against all tested isolates, the result which is in agreement with that of previous studies conducted in Iran, Japan and India 15,24,34,39 . Koga et al 38 showed that the MIC 90 values of LUL for T rubrum and T mentagrophytes were lower than those for other isolates; however, in the present study, it was the most effective drug against all dermatophyte isolates 40 .…”
Section: Discussionsupporting
confidence: 90%
“…Although tinea pedis is not a life‐threatening condition, it is associated with difficulties in performing daily activities, and consequently, affects the quality of life 33 . Previous studies have shown relapses and failure to treat tinea pedis with routine antifungal agents 31,33‐35 . Therefore, reliable diagnosis and efficient treatment of tinea pedis are important.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the evaluation method for viability was developed using qPCR targeting the ITS region of rDNA, which revealed a correlation between ITS DNA and CFU 48 hours after death in T. interdigitale 21 . In addition, the amounts of rDNA in toe nail and skin specimens from patients with tinea pedis and tinea unguium were quantified using the ITS region of rDNA targeted by qPCR 33‐35 . By combining the investigation of rDNA copy numbers with the quantification of rDNA amounts in specimens, it will be possible to estimate the amount of T. interdigitale in affected sites.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, the amounts of rDNA in toe nail and skin specimens from patients with tinea pedis and tinea unguium were quantified using the ITS region of rDNA targeted by qPCR. [33][34][35] By combining the investigation of rDNA copy numbers with the quantification of rDNA amounts in specimens, it will be possible to estimate the amount of T. interdigitale in affected sites. This finding may provide a more detailed understanding of the mechanisms underlying the attenuation and recalcitrance of dermatophytosis caused by T. interdigitale.…”
Section: Discussionmentioning
confidence: 99%
“… 22 qPCR has comparable sensitivity to potassium hydroxide (KOH) examination and nail culture assay by colony-forming unit. 23–25 A total of 12 nails per group (1 or 2 nails per foot) was measured.…”
Section: Methodsmentioning
confidence: 99%